2002
DOI: 10.1515/znc-2002-7-815
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Cadmium Ions by Different Yeast Species

Abstract: Toxicity and accumulation of Cd2+ in yeasts were studied in eight different yeast species. The adaptation to toxic concentration of this metal was dependent on the production of extracellular yeast glycoproteins. The highest concentration of Cd2+ ions in the growth medium was tolerated by a Hansenula anomala, strain while the lowest tolerance was found by the strain of species Saccharomyces cerevisiae. Extracellular glycoproteins of Hansenula anomala absorbed nearly 90% of the total content of Cd2+ ions bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 0 publications
0
36
0
10
Order By: Relevance
“…Some species can control the membrane transport of heavy metals towards, or their active efflux from, the cell [63,64]. Metal ion resistance via transport and passive mechanisms leading to extracellular precipitation is more characteristic for prokaryotes [65], whereas sequestration mechanisms are mainly adopted by eukaryotes [66].…”
Section: Biologically Derived Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some species can control the membrane transport of heavy metals towards, or their active efflux from, the cell [63,64]. Metal ion resistance via transport and passive mechanisms leading to extracellular precipitation is more characteristic for prokaryotes [65], whereas sequestration mechanisms are mainly adopted by eukaryotes [66].…”
Section: Biologically Derived Nanoparticlesmentioning
confidence: 99%
“…Numerous studies have revealed that all yeast genera can accumulate different heavy metals, but particularly interesting is the capability of accumulating significant amounts of highly toxic metals [64]. Cells able to grow in media with high metal ion concentrations are called resistant.…”
Section: Detoxification Mechanisms In Yeastmentioning
confidence: 99%
“…Removal of heavy metals, and radionuclides such as thorium and uranium from aqueous solutions using biological materials and various microorganisms was investigated in several studies. Natural bio-adsorbents such as seaweeds (Yang and Volesky 1999), bacteria (Li et al 2016), yeast (Breierova et al 2002), fungi (Hou et al 2016), algae (Al-Qunaibit, Khalil, and Al-Wassil 2005) and marine sponges (Hansen, Weeks, and Depledge 1995;Maloubier et al 2015) were used in these studies. Biosorption process could be considered as a combined method of passive fusion (coagulation) process independent from the metabolism, and physical and/or chemical adsorption, ion exchange, coordination, complexation, chelate formation and micro-precipitation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, two other studied strains, CCY 19-6-4 and CCY 20-2-33, sorbed Se primarily into cells (63 -74%) and the fibrillar part of cell wall (2 -22%), whereas exopolymers bound only 12 -32% of the total sorbed amount. It is known that metals as Cd, Ni, and Zn are sorbed predominantly onto the fibrillar part of cell walls and exopolymers, and, in this way, the cells are protected from the introduction of the toxic metals into the cells [32] [33]. Exopolymers and cell surface serve as a crucial protective barrier against penetration of the metal ions into the cells and their subsequent damage [34].…”
mentioning
confidence: 99%